1978
DOI: 10.1002/pol.1978.180160607
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic viscosity and translational friction coefficient of nondraining flexible rings with small excluded volume

Abstract: First‐order excluded‐volume effects on the intrinsic viscosity and translational friction coefficient of nondraining flexible ring polymers were calculated on the basis of the Kirkwood–Riseman formalism of polymer hydrodynamics. The cube of the viscosity expansion factor αη,r was found to be represented by α 3η,italicr = 1 + 1.18z + …, where z is the usual excluded‐volume parameter. Combination of this result with the corresponding calculation by Fujita et al., for nondraining linear polymers, yielded α 3η,ita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…Such an experimental g H should not be interpreted as due to small excluded‐volume effects on R H of ring polymers compared to those in linear chains. In fact, our g H is always greater for a larger a , consistent with the first‐order perturbation prediction18, 30 that the hydrodynamic‐radius expansion factor α H (≡ R H / R H0 ) is larger for a ring molecule than for the corresponding linear chain; note that g H / g H0 = α H ( r )/α H ( l ).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Such an experimental g H should not be interpreted as due to small excluded‐volume effects on R H of ring polymers compared to those in linear chains. In fact, our g H is always greater for a larger a , consistent with the first‐order perturbation prediction18, 30 that the hydrodynamic‐radius expansion factor α H (≡ R H / R H0 ) is larger for a ring molecule than for the corresponding linear chain; note that g H / g H0 = α H ( r )/α H ( l ).…”
Section: Resultssupporting
confidence: 85%
“…They exhibit damped oscillation for x smaller than 30, manifesting the locally helical conformation of amylose. The ratios of 〈 S 2 〉 and R H for a perturbed cyclic chain to the respective radii for the corresponding linear chain can be slightly lower than or comparable to the (asymptotic) Gaussian‐chain values unless x is sufficiently large, while excluded‐volume effects on these properties of cycloamylose are always larger than those in linear amylose with the same x , consistent with the predictions from the first‐order perturbation calculations18, 30, 31 and earlier simulations22, 23 on ideally flexible chains. The relation between the radius expansion factors for the two types of amylose is accurately represented by the one derived from the first‐order perturbation expressions or by the interpolation expression constructed in this work.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In previous work, 6 we found that the following relations derived from the first-order perturbation equations 24,25 approximately hold for Monte Carlo data for the expansion factors ␣ H (r), ␣ s 2 (r), and ␣ s 2 (l ) if ␣ s 2 (r) is smaller than 1.6:…”
Section: Appendixmentioning
confidence: 93%